Bridging Policy and Practice: Integrating Indigenous Knowledge and Value-Based Education in Primary School Curriculum under the Indian National Education Policy - Archana Pujar (Journal of Elementary Education Research and Practice, 2026)
This study examines the integration of Indigenous Knowledge Systems (IKS) and value-based education into primary school curricula under India’s National Education Policy 2020 (NEP 2020), with a particular focus on bridging the gap between policy intentions and classroom practices. Employing an integrative literature review and policy analysis, the study synthesizes policy documents, conceptual works, curriculum studies, and empirical literature related to IKS, value-based education, and curriculum implementation in Indian education. The findings reveal that although NEP 2020 provides a strong philosophical foundation for culturally rooted and holistic education, its implementation remains uneven due to limited operational guidance, inadequate teacher preparedness, insufficient contextual learning resources, and persistent structural constraints. The study further demonstrates that IKS and value-based education are mutually reinforcing, as Indigenous knowledge provides a culturally grounded context for ethical, moral, and social development. Teacher agency also emerges as a critical mediating factor in translating policy principles into classroom practices. The novelty of this study lies in its development of a policy–pedagogy–teacher agency framework for integrating IKS and value-based education in primary education under NEP 2020. By linking policy orientation, pedagogical practice, and teacher agency, this study contributes to the literature on culturally responsive curriculum reform and offers practical implications for policymakers, curriculum developers, teacher educators, and primary school practitioners seeking to advance context-sensitive and value-oriented education.